China's New Energy Geopolitics: The Shanghai Cooperation Organization and Central Asia - Ralph Wrobel (ASIEN, 2014)
As China is dependent on oil and gas imports to maintain its high growth rates, the Shanghai Cooperation Organization (SCO) and Central Asia have become increasingly important for the country's economic development. In May 2014, China and Russia signed a new gas deal, for example, and in recent years China has been able to improve its energy security by making several oil and gas agreements with Central Asian countries. This paper focuses on the growth of trade in energy resources from Central Asia and Russia to China. It discusses why energy security, Central Asia and the SCO are so important to the Chinese political elite. Is the PRC's energy security leading to a shift of geopolitical power in the region and what advantages and disadvantages can this shift have for the various parties concerned? The paper shows that the balance of power in the region has basically shifted in China's favour.
Keywords: F02; F55; 330; Shanghai Cooperation Organization; China; Energiepolitik; Geopolitik; China